2011
DOI: 10.1007/s11940-011-0145-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients With Atherosclerotic Carotid Occlusion

William J. Powers

Abstract: • Patients with acute ischemic stroke due to atherosclerotic carotid artery occlusion (ACAO) should receive intravenous tissue plasminogen activator (alteplase) if they meet eligibility criteria of the National Institute of Neurological Disorders and Stroke (NINDS) or the European Cooperative Acute Stroke Study III (ECASS III). • Patients with acute stroke due to ACAO who are not eligible for intravenous tissue plasminogen activator should receive aspirin. Heparin or heparin-like drugs do not improve outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…As a result, establishing patency of the ICA and ECA is essential prior to an intervention. [13,14,15]. Several small series reported in the literature have shown excellent revascularization results in relieving the symptoms of cerebral ischemia.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…As a result, establishing patency of the ICA and ECA is essential prior to an intervention. [13,14,15]. Several small series reported in the literature have shown excellent revascularization results in relieving the symptoms of cerebral ischemia.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…While these studies are highly sensitive, they can often misclassify high-grade stenosis as an occlusion (pseudo-occlusion) [19]. Since the management of carotid occlusion and high-grade stenosis may be different [4], a catheter-based study is essential in characterizing the true degree of stenosis and to further clarify the nature of collateral anastomosis. All 3 patients in this study demonstrated collateral flow through the posterior communicating and ophthalmic arteries, which likely accounts for the mildness of the presenting symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with bilateral carotid occlusion were excluded from the Carotid Occlusion Surgery study as PET imaging cannot be reliably applied as selection criteria in the context of bihemispheric disease. The best management of this subset of patients is unclear [4]. …”
Section: Introductionmentioning
confidence: 99%
“…3,4 To address this issue, we analyzed data from the nonsurgical group of the Carotid Occlusion Surgery Study (COSS).…”
Section: Classification Of Evidencementioning
confidence: 99%
“…[1][2][3] Disagreement exists whether strict blood pressure (BP) control is the best medical management for these patients or whether higher BPs are needed to preserve cerebral perfusion and prevent subsequent stroke. 3,4 To address this issue, we analyzed data from the nonsurgical group of the Carotid Occlusion Surgery Study (COSS). 2 …”
mentioning
confidence: 99%